ANALYSIS OF JUNIOR HIGH SCHOOL STUDENT’S MATHEMATICAL LITERACY ABILITY IN RME-BASED MATHEMATICS LEARNING IN VIEW OF SELF-EFFICACY - Mirtasari, Agustina (FKIP Universitas Muhammadiyah Tangerang, 2024)
Mathematical literacy is a skill that a person must master in the context of construction, application and interpretation to obtain solutions to problems encountered in everyday life and can be influenced by self-efficacy. This research has several objectives as follows: (1) Describe the self-efficacy abilities of students at SMP Negeri 2 Todanan. (2) Describe the mathematical literacy abilities of students at SMP Negeri 2 Todanan in RME-based learning. (3) Knowing students' mathematical literacy abilities in RME-based learning in terms of self-efficacy. This research applies a qualitative approach, namely an approach that aims to identify events that occur in research subjects, such as behavior, motivation, perceptions, activities, etc. This research used instruments in the form of a self-efficacy questionnaire, written tests related to material simplifying algebra based on Mathematical Realistic Education, and documentation. The results of this research state that students with high mathematical literacy skills tend to have high self-efficacy abilities. Students with moderate mathematical literacy skills tend to have moderate self-efficacy abilities. Students with low mathematical literacy abilities tend to have low self-efficacy abilities as well